Cyber Threats Unveiled: From Terrorism to Warfare - Hirenkumar Thakor; Bhavin Mehta (International Journal of Information Security Engineering, 2025)
The paper offers a detailed study of cyber security intimidations, cyber extremism, and cyber warfare in the worldwide context. It touches upon the progress of cyber intimidations from discrete hackers to state-supported actors, exploratory mutual attack vectors such as malware and phishing. The conversation probes into the features of cyber extremism and the inspirations driving such actions. Besides, it clarifies the idea of cyber warfare, as well as strategies and case studies of distinguished occurrences. Lawful and moral deliberations in cyberspace, together with mitigation tactics and upcoming opportunities, are also scrutinized. Through producing historical viewpoints, existing difficulties, and projected growths, the paper emphasizes the imperative for cooperative exertions to improve cyber flexibility and combat evolving intimidations.
Keywords: Cyber flexibility; attack vectors; cooperative efforts; malicious actors; state-supported actors